Deploying Orientalism in culture and history : from Germany to Central and Eastern Europe - Hodkinson, James R., 1973-; Walker, John, 1956 January 14- (Studies in German literature, linguistics, and culture., 2013)
Focuses on the cultural, philosophical, political, and scholarly uses of ""orientalism"" in the German-speaking and Central and Eastern European worlds from the late eighteenth century to the present day.